Bilateral sural nerve harvest in adult patients: a plastic surgery medical residency experience in Brazil - de Menezes Neto, Balduino Ferreira [UNESP]; Viterbo, Fausto [UNESP]; Secanho, Murilo Sgarbi [UNESP]; Moragas, Weber Ribolli [UNESP]; Carvalho, Laísa Brandão [UNESP] (Springer Nature, 2021)
Background: Sural nerve is an excellent nerve for harvest and reconstructive applications for plastic surgeons and should be learned since medical residency. The purpose of this study was to evaluate the number of patients undergoing bilateral removal of the sural nerve in a training center and to investigate if there is a difference in symptoms after 30 months of follow-up. Methods: In this study, adult male patients were selected by convenience sampling method, who agreed to answer the questionnaire electronically and by telephone regarding symptoms after bilateral sural nerve removal. Data were tabulated and analyzed for comparison with the literature. Results: Forty patients answered the questionnaire completely, and only one patient with more than 30 months of surgery had pain (p = 0.12). Twenty-three patients (57.5%) did not have any problems secondary to bilateral sural nerve removal (p = 0.96). Conclusion: Removal of the sural nerve in plastic surgery training services is a safe and well-accepted method for patients. Level of evidence: Level IV, risk / prognostic study.
Keywords: Bilateral sural nerve harvest; Medical residency; Nerve graft; Plastic surgery residents; Reconstructive plastic surgery